2013
DOI: 10.1002/ajmg.c.31371
|View full text |Cite
|
Sign up to set email alerts
|

Implications of genetic testing in noncompaction/hypertrabeculation

Abstract: Noncompaction/hypertrabeculation is increasingly being recognized in children and adults, yet we understand little about the causes of disease. Genes associated with noncompaction/hypertrabeculation have been identified, but how can these assist in clinical management? Genomic technologies have also expanded tremendously, making testing more comprehensive, but they also present new questions given the tremendous diversity of phenotypes and variability of genomes. Here we present genetic evaluation strategies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In addition to sarcomere-encoding genes and the cytoskeleton, mutations in the sodium channel gene, SCN5A, is associated wtih LVNC and rhythm disturbance [63]. Diagnostic testing in patients with LVNC appear to have a detection rate of clinically significant variants in 35-40% of individuals, with sarcomere-encoding genes most commonly found to be mutated [4, 70]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition to sarcomere-encoding genes and the cytoskeleton, mutations in the sodium channel gene, SCN5A, is associated wtih LVNC and rhythm disturbance [63]. Diagnostic testing in patients with LVNC appear to have a detection rate of clinically significant variants in 35-40% of individuals, with sarcomere-encoding genes most commonly found to be mutated [4, 70]. …”
Section: Introductionmentioning
confidence: 99%
“…Considering the hereditary and familial pattern of NCLV [ 17 ] and the correlation between genotype and phenotype of NCLV, a genetic study is suggested in all patients to help the physician have a better estimation of patients’ prognosis [ 18 , 19 ]. However, we could only perform whole exome sequencing (WES) analysis in five cases, which showed different genes ( SCNIB , ALPK3 , IGF2BP2 , BAG3 , MYH7 , MYBPC3 , DSP , TTN , and DSC2 ); a genetic study of the family members also diagnosed cardiomyopathy in the mother of one of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no mechanisms to prevent LVNC or to return gain of cardiac function. While genetic testing can be done to identify gene mutations (Table 1) and determine the risk of passing these mutations to offspring, there are not therapeutic options to actively treat these gene mutations [74]. Future therapy that promotes personalized gene therapy could be a useful tool in treating LVNC.…”
Section: Schematic Overview Of Influencing Factors In Myocardial Nonc...mentioning
confidence: 99%